Dans l’atelier du Métadictionnaire : restituer un savoir lexical ancien par un balisage en XML-TEI, des principes méthodologiques à la pratique numérique - Nathalie Rousseau (Humanités Numériques)
This paper presents the practical aspects of the production of the Multilingual Medical Metadictionary of the Medica Digital Library, a project funded by the Collex-Persée research infrastructure. We highlight how, during the process of selectively tagging in TEI XML the OCRised text of several ancient medical dictionaries, the principles adopted (provide reliable data from a philological point of view, stick to the analyses provided by the dictionaries, preserve unprocessed information) interacted with digital practice. We describe the trade-offs that have been made in order to deliver already quite comprehensive results as quickly as possible, while trying to maintain philological accuracy, and we indicate the areas for improvement that have been identified.